catena-Poly[[diphenyltin(IV)]-di-μ-isothiocyanato]: an unprecedented layered coordination polymer resulting from bridging κ2N:S thiocyanato ligands - Ann-Kathrin Pancratz; Anne Kamrowski; Hans Reuter (IUCrData, 2024)
In the title compound, diphenyltin(IV) diisothiocyanate, [Sn(NCS)2(C6H5)2]n or Ph2Sn(NCS)2, comparatively long tin–nitrogen and short tin–sulfur bonds prove that the ambidentate isothiocyanate ion acts as a bridge between two neighboring, octahedrally coordinated tin atoms. As a result, the molecules lose their individuality in favor of a layered coordination polymer that represents a new type of molecular interactions in the structural chemistry of diorganotin(IV) dihalides/pseudohalides. The tin atom is located on a center of inversion.